Stroke Prevention With the PCSK9 (Proprotein Convertase Subtilisin-Kexin Type 9) Inhibitor Evolocumab Added to Statin in High-Risk Patients With Stable Atherosclerosis - Giugliano, Robert P; Pedersen, Terje R; Saver, Jeffrey L; Sever, Peter S; Keech, Anthony C; Bohula, Erin A; Murphy, Sabina A; Wasserman, Scott M; Honarpour, Narimon; Wang, Huei; Lira Pineda, Armando; Sabatine, Marc S (Stroke (1970), 2020)
Background and Purpose- The PCSK9 (proprotein convertase subtilisin-kexin type 9) monoclonal antibody evolocumab lowered LDL (low-density lipoprotein) cholesterol by 59% to 0.8 (0.5-1.2) mmol/L and significantly reduced major vascular events in the FOURIER trial (Further Cardiovascular Outcomes Research with PCSK9 Inhibition in Subjects with Elevated Risk). Herein, we report the results of a prespecified analysis of cerebrovascular events in the overall trial population and in patients stratified by prior stroke. Methods- FOURIER was a randomized, double-blind trial comparing evolocumab versus placebo in patients with established atherosclerosis, additional risk factors, and LDL cholesterol levels ≥1.8 (or non-HDL [high-density lipoprotein] ≥2.6 mmol/L) on statin therapy. The median follow-up was 2.2 years. We analyzed the efficacy of evolocumab to reduce overall stroke and stroke subtypes, as well as the primary cardiovascular composite end point by subgroups according to a history of stroke. Results- Among the 27 564 patients, 469 (1.7%) experienced a total of 503 strokes of which 421 (84%) were ischemic. Prior ischemic stroke, diabetes mellitus, elevated CRP (C-reactive protein), history of heart failure, older age, nonwhite race, peripheral arterial disease, and renal insufficiency were independent predictors of stroke. Evolocumab significantly reduced all stroke (1.5% versus 1.9%; hazard ratio, 0.79 [95% CI, 0.66-0.95]; =0.01) and ischemic stroke (1.2% versus 1.6%; hazard ratio, 0.75 [95% CI, 0.62-0.92]; =0.005), with no difference in hemorrhagic stroke (0.21% versus 0.18%; hazard ratio, 1.16 [95% CI, 0.68-1.98]; =0.59). These findings were consistent across subgroups, including among the 5337 patients (19%) with prior ischemic stroke in whom the hazard ratios (95% CIs) were 0.85 (0.72-1.00) for the cardiovascular composite, 0.90 (0.68-1.19) for all stroke, and 0.92 (0.68-1.25) for ischemic stroke ( interactions, 0.91, 0.22, and 0.09, respectively, compared with patients without a prior ischemic stroke). Conclusions- Inhibition of PCSK9 with evolocumab added to statin in patients with established atherosclerosis reduced ischemic stroke and cardiovascular events in the total population and in key subgroups, including those with prior ischemic stroke. Registration- URL: https://www.clinicaltrials.gov; Unique identifier: NCT01764633.